ENZYME INHIBITION - ENVIRONMENTAL AND BIOMEDICAL APPLICATIONS - Baskar, G. (Frontiers in Enzyme Inhibition Ser., 2020)
Enzyme inhibitors play a pivotal role in pharmaceutical and nutraceutical industries. The primary understanding of the action of inhibitors helps pharmacologists during the design process for developing new therapeutic drugs. Most drugs treat various chronic and life threatening diseases owing to their specificity and the potency of enzymes which they can inhibit. Enzyme inhibitors are used to screen various levels of diseases which propel the growth of inhibitors. The potential for enzyme inhibitors in the therapeutics market is very high as the biochemical properties and classes of enzyme in.